1994
DOI: 10.1007/bf00019486
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the BnmNAP subfamily of napin genes coincides with the induction of Brassica microspore embryogenesis

Abstract: Brassica napus cv. Topas microspores can be diverted from pollen development toward haploid embryo formation in culture by subjecting them to a heat stress treatment. We show that this switch in developmental pathways is accompanied by the induction of high levels of napin seed storage protein gene expression. Changes in the plant growth or microspore culture conditions were not by themselves sufficient to induce napin gene expression. Specific members of the napin multigene family were cloned from a cDNA libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 48 publications
(73 reference statements)
3
49
0
Order By: Relevance
“…To reduce the chance of cloning genes induced specifically by the heat-stress treatment, we used RNA from microspores cultured at 25 Њ C for 24 h followed by culture at 32.5 Њ C for 72 h (Pechan et al, 1991;Boutilier et al, 1994) in the construction of a subtracted probe. Although these microspores have been heat stressed, they do not form embryos upon transfer to 25 Њ C, nor do they continue dividing to form mature pollen grains.…”
Section: Isolation Of Early Embryo-expressed Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce the chance of cloning genes induced specifically by the heat-stress treatment, we used RNA from microspores cultured at 25 Њ C for 24 h followed by culture at 32.5 Њ C for 72 h (Pechan et al, 1991;Boutilier et al, 1994) in the construction of a subtracted probe. Although these microspores have been heat stressed, they do not form embryos upon transfer to 25 Њ C, nor do they continue dividing to form mature pollen grains.…”
Section: Isolation Of Early Embryo-expressed Genesmentioning
confidence: 99%
“…The Brassica plant growth and microspore culture conditions have been described previously (Boutilier et al, 1994).…”
Section: Microspore Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Based on their existence in various plants at various stages and in various locations, many BURP family members are involved in maintaining normal plant metabolism and development. For example, in the oilseed rape (Brassica napes L.), BNM2 is induced at the beginning of microspore embryogenesis, whereas the corresponding protein remains confined to the seed, where it is localized in the protein storage vacuoles (Zheng et al 1992, Boutilier et al 1994. Teerawanichpan et al 2009, Treacy et 1997.…”
Section: Similarity Searchmentioning
confidence: 99%
“…These events include structural and cellular changes during the first divisions (Dubas et al 2011;Hause et al 1993;Satpute et al 2005;Telmer et al 1995;Zaki and Dickinson 1990), changes in DNA synthesis and gene expression (Binarova et al 1993;Boutilier et al 1994;Hays et al 1999;Seguí-Simarro et al 2011a), the role of epigenetic modifications Rodríguez-Sanz et al 2014;Solís et al 2012), regulatory cascades ( (Cordewener et al 2000;Cordewener et al 1994;Pechan et al 1991), with special focus on heat-shock proteins expression (Cordewener et al 1995;Seguí-Simarro et al 2003;Testillano et al 2000;Zhao et al 2003). Comparative studies between MDEs and zygotic embryos (Ilic-Grubor et al 1998;Yeung et al 1996) have shown that MDEs may hold a high morphologic similarity to zygotic embryos, and they can be used as a model to study general embryogenesis characteristics, as well as the role of different plant hormones during embryogenesis initiation and embryo development (Belmonte et al 2010;Hays et al 2001;Hays et al 2000;Hays et al 2002;Robert et al 2015).…”
Section: Dh36 Embryogenic Response Approaches That Of the Model Speciesmentioning
confidence: 99%